2017
DOI: 10.1371/journal.pone.0183252
|View full text |Cite
|
Sign up to set email alerts
|

Facilitatory and inhibitory pain mechanisms are altered in patients with carpal tunnel syndrome

Abstract: Preliminary evidence from studies using quantitative sensory testing suggests the presence of central mechanisms in patients with carpal tunnel syndrome (CTS) as apparent by widespread hyperalgesia. Hallmarks of central mechanisms after nerve injuries include nociceptive facilitation and reduced endogenous pain inhibition. Methods to study nociceptive facilitation in CTS so far have been limited to quantitative sensory testing and the integrity of endogenous inhibition remains unexamined. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
3
24
0
3
Order By: Relevance
“…These sensory deficits are not associated with electrodiagnostic findings suggesting that sensitization is not related to the damage of the median nerve but rather can be present from the onset of the condition (9). A recent study confirming the hypothesis of altered central pain processing in CTS has shown that patients not only exhibit increased pain facilitation but that they also have reduced endogenous pain inhibition (10). Nevertheless, other studies have not found widespread sensory changes in patients with CTS without concomitant neck pain suggesting that there might be subgroups of subjects with CTS with varying levels of sensitivity (11).…”
Section: Introductionmentioning
confidence: 92%
“…These sensory deficits are not associated with electrodiagnostic findings suggesting that sensitization is not related to the damage of the median nerve but rather can be present from the onset of the condition (9). A recent study confirming the hypothesis of altered central pain processing in CTS has shown that patients not only exhibit increased pain facilitation but that they also have reduced endogenous pain inhibition (10). Nevertheless, other studies have not found widespread sensory changes in patients with CTS without concomitant neck pain suggesting that there might be subgroups of subjects with CTS with varying levels of sensitivity (11).…”
Section: Introductionmentioning
confidence: 92%
“…A pro-nociceptive pattern of amplified pain facilitation (central sensitization) and reduced endogenous pain inhibition is also common in carpal tunnel syndrome, chronic pancreatitis (Soon, Vicenzino, Schmid, & Coppieters, 2017), whiplash-associated disorders (Daenen et al, 2013; Ng, Pedler, Vicenzino, & Sterling, 2014; Yarnitsky, 2015) and in primary headaches such as migraine, chronic tension-type headache and chronic post-traumatic headache following mild traumatic brain injury (Sandrini et al, 2006). In patients with acute and chronic low back pain, CPM effect is triggered following counter-irritation, but its duration is significantly reduced compared to healthy individuals (Mlekusch et al, 2016).…”
Section: Clinical Relevance Of Pain Modulationmentioning
confidence: 99%
“…Central changes after severe experimental nerve injury include, but are not limited to, central immune-inflammatory mechanisms, 81 , 101 , 122 , 123 central sensitisation, 80 and changes to cortical representations. 43 , 104 , 105 , 150 Clinical hallmarks of central mechanisms including bilateral sensory deficits in unilateral painful entrapment neuropathies, 29 , 37 , 59 , 142 widespread hypersensitivity, 37 , 53 , 142 , 171 , 172 and impaired conditioned pain modulation 138 have been described in patients with entrapment neuropathies. Furthermore, cortical changes have been reported including functional and structural changes of the somatosensory cortex in patients with CTS 43 , 93 , 104 , 150 and changes in cortical morphometry in patients with lumbar radicular pain.…”
Section: Pathophysiologymentioning
confidence: 99%